2008
DOI: 10.1590/s0100-67622008000200016
|View full text |Cite
|
Sign up to set email alerts
|

Resposta estomática e produção de matéria seca em plantas jovens de aroeira submetidas a diferentes regimes hídricos

Abstract: RESUMO -Este trabalho objetivou avaliar a transpiração, resistência difusiva do vapor d'água, a produção de matéria seca e alocação de biomassa em plantas jovens de aroeira submetidas a déficit hídrico. Foram utilizadas mudas de Schinus terebinthifolius Raddi com três meses de idade, cultivadas em vasos de polietileno contendo 5,5 kg de terriço vegetal. O delineamento experimental foi inteiramente casualizado com quatro tratamentos hídricos (100% da capacidade de campo (CC), 75% CC, 50% CC e 25% CC) e quatro r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
(8 reference statements)
2
8
0
10
Order By: Relevance
“…Galmés et al (2007) investigated eight Mediterranean species subjected to water stress, and also reported a decrease in conductance by increasing the hydric failure, with a recovery of conductance rates after rehydration. This result was similar to that one reported by Silva et al (2008) with Schinus terebinthifolius Raddi. According to Larcher (2010) and Akınci and Lösel (2012), some species can exhibit slow recovery of stomatal conductance due to the buildup of abscisic acid (ABA) during water stress with the recovery times varying according to the species.…”
Section: Stomatal Conductancesupporting
confidence: 93%
See 1 more Smart Citation
“…Galmés et al (2007) investigated eight Mediterranean species subjected to water stress, and also reported a decrease in conductance by increasing the hydric failure, with a recovery of conductance rates after rehydration. This result was similar to that one reported by Silva et al (2008) with Schinus terebinthifolius Raddi. According to Larcher (2010) and Akınci and Lösel (2012), some species can exhibit slow recovery of stomatal conductance due to the buildup of abscisic acid (ABA) during water stress with the recovery times varying according to the species.…”
Section: Stomatal Conductancesupporting
confidence: 93%
“…As reported by Tatagiba et al (2007), it was observed a decrease in transpiration rates during drought periods and an increase during rainy periods for Eucaliptus clones, while Silva et al (2008) have reported a similar pattern for S.…”
Section: Transpiration Ratessupporting
confidence: 65%
“…According to Silva et al (2008), water deficiency conditions are capable of affecting the stomatal apparatus by causing the stomata to close. In this same context, Yordanov et al (2003) state that in a water deficit condition, the first defense adopted by the plant would be the restriction of the stomatal opening.…”
Section: Discussionmentioning
confidence: 99%
“…Then, it can be noticed a significant reduction for this variable when the plants were under the effects of water stress at 40% of the MWHC (reduction of 52% compared to the control treatment). Silva et al (2008) reported that for the production of dry matter in young plants of 'aroeira' (Schinus terebinthifolius Raddi) there was no significant difference among the treatments for the allocation of biomass to the leaf (BAL), stems (BAS), and roots (BAR). In neem plants (Azadirachta indica A. Juss), Martins et al (2010) found that for the control 100%, 80%, and 60% of the MWHC, the biomass allocation to the leaves at the end of the experiment was the highest, being 38.9, 40.1, and 43.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%